PENGARUH PENYAJIAN LAPORAN PERTANGGUNGJAWABAN AKSESIBILITAS DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA LAWANG URU KECAMATAN BANAMA TINGANG KABUPATEN PULANG PISAU - Lala Silvia; Sri Yuni; Oktobria Y Asi (Universitas Palangka Raya, 2023)
The purpose of this study was to determine the effect of the accountability report presentation, accessibility and system control systems on the accountability of Village Fund Allocation (ADD) management in Lawang Uru Village, Banama Tingang District, Pulang Pisau Regency. The research method used is quantitative research methods. The population in this study were all RT, BPD, Village Heads and Lawang Uru community, Banama Tingang District, Pulang Pisau Regency as many as 17 respondents. Respondents in this study consisted of RT, BPD, Kaur, secretary and the Head of Lawang uru village, banama tingang district, home knife district as many as 17 respondents. The dependent variable of this study is accountability (Y). The independent variables include: accountability report presentation (X1) accessibility (X2) internal control system (X3) and accessibility accountability report presentation and internal control system (X4). For the data analysis method using multiple linear regression. The results of this study indicate that the accountability report presentation, accessibility, has a significant positive effect on the accountability of Village Fund Allocation (ADD) management in Lawang Uru Village, Banama Tingang District, Pulang Pisau Regency. whereas the internal control system and the effect of the accountability report presentation, accessibility and internal control system did not have a significant positive effect on the accountability of the Village Fund Allocation (ADD) management in Lawang Uru Village, Banama Tingang District, Pulang Pisau Regency. The variable that has the highest t-count value is the variable in the accountability report presentation. This means that accountability is driven more by the presentation of accountability reports